STUDI PENGARUH JENIS DAN KOMPOSISI KATALIS PADA PROSES PERTUMBUHAN CARBON NANOTUBE (CNT) DENGAN METODE CATALYTIC CHEMICAL VAPOUR DEPOSITION (CCVD) - Retno Sutanti; Susi Handayani (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Abstract Carbon nanotube is one of the nanotechnology that applicated in a variety of science such as electronics, chemistry and etc. In this research staked with system Catalytic Chemical Vapour Deposition (CCVD) process to syntheses Carbon nanotubes from acetylene gas using Co/Al2O3 and Fe/Al2O3 catalysts with catalyst heavy 0,3 gram,operation temperature 700oC, flow rate rasio of N2 and acetylene gas is 1 : 1. From analysis result by Scanning Electron Microscopy (SEM), CNT was formed MWNT type with difference diameter, where in order to larger active component concentration resultant diameter of CNT larger. Whereas product severe sintheses result turn inside out collating with active component. The larger of active component, product weight syntheses result smaller. For Fe/Al2O3 catalyst was given CNT diameter larger compared with CNT syntheses used Co/Al2O3. catalysts.